2014
DOI: 10.1371/journal.pone.0085793
|View full text |Cite
|
Sign up to set email alerts
|

TL1A Induces TCR Independent IL-6 and TNF-α Production and Growth of PLZF+ Leukocytes

Abstract: An elevated level of the cytokine TL1A is known to be associated with several autoimmune diseases, e.g. rheumatoid arthritis and inflammatory bowel disease. However, the mode of action of TL1A remains elusive. In this study, we investigated the role of TL1A in a pro-inflammatory setting, using human leukocytes purified from healthy donors. We show that TL1A, together with IL-12, IL-15 and IL-18, directly induces the production of IL-6 and TNF-α from leukocytes. Interestingly, TL1A-induced IL-6 was not produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
(84 reference statements)
3
16
0
Order By: Relevance
“…In addition, aberrant expression of NKG2D or its ligands on IELs is associated with various gut‐related inflammatory diseases, such as Crohn's and coeliac diseases . The decrease in NKG2D on IEL subsets in TL1A KO mice is in accordance with in vitro stimulation studies we have performed, showing that stimulation with TL1A specifically induce the upregulation of NKG2D on human peripheral blood lymphocytes (PBLs) . Thus, less NKG2D expression indicates that the IELs in the TL1A KO mice are less capable of detecting stress in the surrounding epithelial cells than WT mice.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, aberrant expression of NKG2D or its ligands on IELs is associated with various gut‐related inflammatory diseases, such as Crohn's and coeliac diseases . The decrease in NKG2D on IEL subsets in TL1A KO mice is in accordance with in vitro stimulation studies we have performed, showing that stimulation with TL1A specifically induce the upregulation of NKG2D on human peripheral blood lymphocytes (PBLs) . Thus, less NKG2D expression indicates that the IELs in the TL1A KO mice are less capable of detecting stress in the surrounding epithelial cells than WT mice.…”
Section: Discussionsupporting
confidence: 76%
“…In combination with IL-12 and IL-18, TL1A supports IFN-γ production by T cells and NK cells [10], and induces proliferation of human NK, NKT and other T cells in vitro [11][14]. We have recently shown that TL1A together with IL-12, IL-15 and IL-18 induces IL-6 and TNF-α production in leukocytes purified from healthy donors [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that stimulation of PBMCs with TL1A in combination with IL‐12 + IL‐18 has a synergistic effect on proliferation and secretion of other inflammatory cytokines, such as TNF‐α and IL‐6 . Here, the impact of the different cytokines on cellular activation is illustrated both by a representative healthy donor (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…TCR‐independent activation of T cells with cytokines, such as IL‐12 and IL‐18, is a relatively new approach in terms of chronic inflammatory diseases. We recently found that in vitro addition of TL1A to (IL‐12 and IL‐18)‐stimulated lymphocytes, yielded TL1A‐specific expression of TNF‐α and IL‐6 as well as increased proliferation . Such cytokine induced activation, specifically induce proliferation of memory T cells, NK cells and NKT cells.…”
Section: Discussionmentioning
confidence: 99%